Hubungan Depresi, Asupan, dan Penampilan Makanan dengan Sisa Makan Pagi Pasien Rawat Inap (Studi di Rumah Sakit Islam Jemursari Surabaya) - Rizka Amalia Habiba; Merryana Adriani (Amerta Nutrition, 2017)
Background: Food waste problem in some hospitals in Indonesia is still quite high at >20%. The proportion of residual high enough lies in the morning meal. This results in inadequate nutrition intake so that it affects the length of stay and increases patient morbidity and mortality. Food waste can be due to individual factors, dietary habits, food intake, and food quality.Objectives: This study aims to analyze the relationship of depression, intake, and appearance of food with the waste of the morning meal in hospitalized patients.Methods: This was a cross sectional study involving 47 respondents that was chosen using a simple random sampling technique at the RSI Jemursari Surabaya. Morning food waste was collected for measurement using food scale; patient’s psychological condition, food intake and appearance of food were measured using questionnaires. Statistical analysis used was Spearman and Chi Square test. Results: Most of the respondents did not experience anxiety and depression disorder. Most respondents have less energy and protein intake. There was a relationship between depression (p=0.02) and energy intake (p=0.035) with the waste of the morning meal. There is a relationship of protein intake in the morning with the rest of the animal side (p = 0.002). However, there was no correlation between appearance (p = 0.64), large portion (p = 0.4), and presentation method (p=0.83) with waste of the morning meal.Conclusion: Food waste can be affected by a person's depression and food intake. Feeding the patient not only comes from hospital food alone, but from outside the hospital as well. However, food outside the hospital does not affect the intake so that the higher the patient leaves the food, the lower the intake of energy and protein. Communication and education should be done to patients to try to spend the food and pay attention to the intake.ABSTRAK Latar Belakang: Permasalahan sisa makanan di beberapa rumah sakit di Indonesia masih cukup tinggi  yaitu >20%. Proporsi sisa yang cukup tinggi terletak pada makan pagi. Hal ini mengakibatkan asupan gizi tidak adekuat sehingga berdampak pada lamanya rawat inap dan meningkatkan morbiditas serta mortalitas pasien. Sisa makanan bisa disebabkan dari faktor individu, kebiasaan pola makan, asupan makan, dan mutu makanan.Tujuan: Penelitian ini bertujuan menganalisis hubungan depresi, asupan, dan penampilan makanan dengan sisa makanan pagi pada pasien rawat inap.Metode: Merupakan penelitian observasional analitik studi cross sectional dengan sampel penelitian sebesar 47 pasien terpilih secara simple random sampling berada di RSI Jemursari Surabaya. Pengumpulan data meliputi penimbangan sisa makan pagi, wawancara keadaan psikis, asupan makan, dan penampilan makan pagi. Analisis data menggunakan uji spearman dan chi square.Hasil: Diketahui sebagian besar responden tidak mengalami gangguan kecemasan dan depresi. Sebagian besar responden memiliki asupan energi dan protein yang kurang. Terdapat hubungan yang bermakna antara depresi (p=0,02) dan asupan energi (p=0,035) dengan sisa makanan pagi. Terdapat hubungan asupan protein pagi dengan sisa lauk hewani (p=0,002). Namun tidak terdapat hubungan antara penampilan yaitu warna (p=0,64), besar porsi (p=0,4), dan cara penyajian (p=0,83) dengan sisa makan pagi.Kesimpulan: Sisa makanan dapat dipengaruhi dari depresi seseorang dan asupan makannya. Asupan makan pasien tidak hanya berasal dari makanan rumah sakit saja, melainkan dari luar rumah sakit juga. Namun, makanan luar rumah sakit tidak mempengaruhi asupan sehingga semakin tinggi pasien menyisakan makanannya, maka semakin rendah asupan energi dan protein. Sebaiknya perlu dilakukan komunikasi dan edukasi kepada pasien supaya berusaha menghabiskan makanannya dan memperhatikan asupannya.